Elementos de la teoría semiótica de la percepción de Peirce para el desarrollo de interfaces de recuperación de información - Baptista, Fabricio; De Almeida, Carlos Cândido [UNESP]; Ferneda, Edberto [UNESP] (My University, 2017)
This article explores the basic concepts of perception in Charles Sanders Peirce relating them to perceptual processes that affect the design of digital interfaces in the field of information retrieval. For this, it was tried to present the conceptual bases of peircean semiotics, along with other theories related to the perceptive process, as theoretical bases of a Semiotic Engineering. The results of the research indicate that it is appropriate to consider the elements of the process of perception collected by Peirce and the types of mediation (iconic, indicial and symbolic) in the human-computer interaction. Synthesizing, it can be observed that the formation of the thought begins at the doors of perception, making relevant its study for the development of computer interfaces, especially in the scope of information retrieval.
Elements of Peirce’s semiotic theory of perception for the development of information retrieval interfaces
Keywords: Information retrieval interfaces; Peirce, charles sanders; Perception; Semiotics; Theory of perception